THE INFLUENCE OF CAPITAL EXPENDITURE TOWARDS COMPANY’S PROFITABILITY - Hutama, Muhamad Bangkit (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2018)
This research aims to find the influence of capital expenditue investment on company’s profitability. For major business investment projects, capital expenditure have an important role in financial statement. One view is that capital expenditure announcements provide information about a firm’s earnings prospects. The research population covered go-public companies from manufacturing, telecommunication and Oil that listed on Indonesia Stock Exchange for periods, 2012-2016. The method used for selecting the samples is purposive sampling method. Samples used in this research is 27 companies, 135 Data from Manufacturing, Telecommunication and Oil Companies. The research result reveals that Capital Expenditure have a significant influence towards profitability. Keywords: Capital Expenditure, Profitability, Company Financial Performance